Object relations in depression : a return to theory - Lubbe, Trevor, 1952- (Hove, East Sussex : Routledge, 2010)
'This book examines the role of British Object Relations Theory in order to explore our understanding and treatment of depression. It challenges current conceptualizations of depression whilst simultaneously discussing the complex nature of depression, its long lasting and chronic implications and the susceptibility to relapse many may face.Illuminated throughout by case studies, areas of discussion include: Freud's theory of depression, analytic sub-types of depression, a theoretical contribution to the problem of relapse, the correlation between dream work and the work of mourning. Object Relations in Depression offers a psychoanalytic discussion of the multifaceted nature of depression and as such will be of great interest to all those in the psychoanalytic field'--Provided by publisher
(Publisher-supplied data) CHAPTER 1. DEPRESSION TODAY: A CRITICAL POINT IN UNDERSTANDING AND TREAMENT -- CHAPTER 2. FREUD'S THEORY OF DEPRESSION -- CHAPTER 3. KARL ABRAHAM'S THEORY OF DEPRESSION -- CHAPTER 4. MELANIE KLEIN'S THEORY OF DEPRESSION -- CHAPTER 5. WHEN THE BODY GETS DEPRESSED: HENRI REY -- CHAPTER 6. WINNICOTT ON DEPRESSION -- CHAPTER 7. A NOTE ON FAIRBAIRN'S CONCEPT OF'FUTILITY' -- CHAPTER 8. ANALYTIC SUB-TYPES OF DEPRESSION. -- CHAPTER 9. A THEORETICAL CONRIBUTION TO THE PROBLEM OF RELAPSE -- CHAPTER 10. THE CORRELATION BETWEEN DREAM WORK AND THE WORK OF MOURNING -- CHAPTER 11. CASE STUDY: A TYPE OF IDENTICATION FOUND IN DEPRESSION-RELATED LOSS. -- CHAPTER 12. THE DEPRESSED CHILD: THE SCANDAL OF PRESCRIBING ANTIDEPRESSANTS -- CHAPTER 13. FREUD'S DEPRESSION -- CHAPTER 14. KLEIN'S DEPRESSION -- CHAPTER 15 BION'S DEPRESSION
Keywords: Depressive Disorder; Object Attachment; Psychoanalytic Theory